Strategi Penataan Kawasan Dadaha Melalui Pendekatan Tata Bangunan Dan Lingkungan Studi Kasus : Di Kota Tasikmalaya) - Metty Triantika; Jenniria RajaGukguk; Kasman Kasman (Prodi Kajian Pembangunan Perkotaan dan Wilayah, 2022)
The Dadaha area is part of the old CBD of Tasikmalaya City and part of the Tasikmalaya City forest RTH plan and is an urban RTH conservation area and city-scale public space. Based on the function of the Dadaha Area that has been determined, in the existing condition, there are problems or discrepancies. Development in the area, resulting in disruption of community activities and disrupting the main function of the Dadaha Area as Public RTH. Therefore, based on the problems that occur in the Dadaha Area, the purpose of this research is to analyze how the condition of the built-up area, population structure, development of the built-up area, and its suitability for land use policies. Then based on the results of the analysis, a factor analysis will be carried out which is considered influential in the occurrence of built-up area deviations. Based on the results of the analysis conducted, there is a condition of the built-up area that has increased the number and density of buildings from 2016 and 2019, this is in line with the increasing population conditions as well, as well as analysis of projected needs for facilities and infrastructure. There are street vendors located on green lanes, road bodies, and the condition of street vendors is not organized, and their processing does not preserve the environment. Furthermore, based on these results, the concept and formulation of a strategy for controlling built-up areas will be prepared. It is hoped that the formulation of this strategy will be able to organize built-up areas that support the main function of the Dadaha area as a public green space.